Enzymatic purification of glucomannan from Amorphophallus oncophyllus using α-Amylase (Bioscience Journal, 2019)
The international standards for top glucomannan flour require a minimum of 70% glucomannan. The glucomannan content of Amorphophallus oncophyllus flour was approximately 60%, with starch as the major impurity. Elimination of starch was expected to increase the purity of glucomannan. The purpose of this research was to study starch hydrolysis of the flour using Î±-amylase. Temperature (35.5-84.5oC), time (0.4-3.6 h) and pH (2.2-8.8) of hydrolysis were selected as independent variables. A central composite design of response surface methodology (RSM) was performed to obtain the optimum condition. This approach was a novelty of this enzymatic purification of A. oncophyllus. Glucomannan content, starch content, and solubility were chosen as the response variables. The models were reliable for predicting the responses (R2â‰¥ 0.771). It was predicted that the highest glucomannan content (93.0%) obtained at the lowest starch content (1.14%), which hydrolysed at pH 6.17, 84.5oC and 3.6 h. Prior the verification of the optimum hydrolysed condition from the model, the glucomannan and starch content was 81.59% and 2.27%, respectively. After purification, the absorbance of the Î²-1,4 glycosidic bond increased as a sign of higher glucomannan purity. A less rough surface and irregular shape of the grain morphology was observed after purification.